The Big Red One America's legendary 1st Infantry Division - Wheeler, James Scott 1947- (Modern war studies, 2017)
"A thoroughly revised and updated edition of the book first published by UPK in 2007. What's new: Wheeler brings the history of the division up to date. The new chapters cover the peacekeeping missions in the Balkans (1995-2004) and the wars in Iraq and Afghanistan (2001-2017). All of the earlier chapters have been edited to reduce their length by roughly 1500-2000 words each. The introduction and conclusion are new, and Paul Herbert has revised his foreword"...Provided by publisher